High-resolution manometry alters the diagnosis in patients diagnosed with diffuse oesophageal spasm by conventional manometry: resurgence of achalasia cardia. (13th March 2011) - Majumdar, D; Saunders, P; Yiannakou, Y; Dhar, A
Abstract : Introduction: Oesophageal manometry is the gold standard for the diagnosis of oesophageal dysmotility, a common clinical problem. Advances in manometric techniques by high-resolution manometry (HRM) and oesophageal pressure topography have revolutionised the interpretation of oesophageal physiology. There are reports of the impact of HRM to a change in manometric diagnosis. Aim: To study the change in the diagnosis of diffuse oesophageal spasm by HRM and its impact on clinical management of oesophageal dysmotility. Patients and methods: Between 2009 and 2010, all patients with a diagnosis of diffuse oesophageal spasm on conventional manometry referred for endoscopic botulinum toxin treatment were offered HRM at a tertiary referral centre. Case notes review was done for clinical symptoms at presentation, initial and final manometric diagnosis and outcomes of treatment. Results: 10 patients were referred for botulinum toxin treatment of diffuse oesophageal spasm. Presenting symptoms were dysphagia, chest pain, regurgitation and weight loss; 6 patients had more than one symptom. Mean age = 57.6 years with M: F = 1:2. Mean duration between onset of symptoms and referral to specialist service was 20.6 months. All had a normal gastroduodenoscopy. Seven patients had barium swallow showing: hiatus hernia (n=1), oesophageal dysmotility (n=3), probable achalasia (n=2) and normal study (n=1). On conventional manometry, 7 were diagnosed as diffuse oesophageal spasm (DES), 2 were diagnosed with hypertensive oesophageal contractions and one had diffuse dysmotility. Five of these patients had HRM at a tertiary centre. Three patients had features of classic achalasia, one revealed DES and one had functional oesophago-gastric junction (OGJ) obstruction. The patients with achalasia were treated with 100 units of Botulinum toxin injection at the OG junction. 2 of them had complete symptom resolution and remained symptom free at 1 year follow-up. 1 patient with achalasia did not respond and was referred for a laparoscopic cardiomyotomy. Of the 5 patients with DES and hypertensive contractions 2 were treated successfully with Botulinum toxin injection to the OG junction and in the lower body of oesophagus. 3 patients had calcium channel blocker therapy with good symptom resolution. Conclusion: HRM alters the diagnosis of diffuse oesophageal spasm on conventional manometry to achalasia in a third of patients, and therefore has a significant impact on their treatment options. Based on this initial observation, a larger prospective study is planned to investigate this change to diagnosis.